ANTIDIABETIC POTENTIAL OF PLANT-BASED SILVER NANOPARTICLES SYNTHESIZED BY USING THE EXTRACTS OF Moringa oleifera, Abelmoschus esculentus and Catharanthus roseus (Applied Biological Research, 2025)
Diabetes mellitus is an endocrine disorder caused by inadequate insulin or insulin resistance, leading to elevated blood glucose levels. This study aimed to evaluate the anti-diabetic potential of plant-based silver nanoparticles (AgNPs). AgNPs from drumstick (Moringa oleifera), okra (Abelmoschus esculentus), and periwinkle (Catharanthus roseus) were synthesized using a green synthesis approach. Characterization of the plant-based AgNPs was carried out using UV-visible spectroscopy, Fourier transform infrared spectroscopy (FTIR), and field emission scanning electron microscopy (FESEM).UV-visible spectroscopy revealed surface plasmon resonance peaks at 400 nm for M. oleifera-AgNPs (MO-AgNPs) and 401 nm for both C. roseus-AgNPs (CR-AgNPs) and A. esculentus-AgNPs (AE-AgNPs). FTIR analysis identified various functional groups present in the AgNPs. FESEM images showed spherical nanoparticles sized 12–22 nm (AE-AgNPs), 21–46 nm (CR-AgNPs), and 13–49 nm (MO-AgNPs). Dynamic light scattering (DLS) analysis indicated maximum size distributions at 50 nm (CR-AgNPs), 70 nm (AE-AgNPs), and 40 nm (MO-AgNPs).The plant-based AgNPs exhibited significant anti-diabetic activity against carbohydrate-digesting enzymes such as amylase and glucosidase. All three synthesized AgNPs increased α-amylase and α-glucosidase enzyme inhibition. The D-glucose diffusion retardation index (GDRI) of AE-AgNPs and MO-AgNPs was comparable to the standard anti-diabetic drug, acarbose. Thus, these plant-based AgNPs demonstrate promising anti-diabetic potential and may be further explored for use in diabetes-related medicinal formulations.
Keywords: Diabetes; drumstick; green synthesis; okra; periwinkle; silver nanoparticles